Upaya Peningkatan Ketuntasan Hasil Belajar Matematika Siswa Kelas V MIN 2 Kulon Progo dengan Menggunakan Media Video Pembelajaran - Asmawati, Fitri; Sholihah, Dyahsih Alin (Indonesian Journal of Elementary Education and Teaching Innovation, 2024)
Students' learning outcomes, especially in mathematics, are still unsatisfactory because many of them have not reached the KKM. For this reason, it is necessary to improve the results and completeness of students' mathematics learning through the use of educational video media. Thus, the purpose of this study is to describe the improvement of the completeness of the mathematics learning outcomes of MI students in grade V on the material of addition and subtraction of fractions by using learning video media. This research is a classroom action research (PTK) conducted in two cycles. The PTK model used is Kemmis and Mc Taggart's model with four stages namely planning, implementation, observation and reflection. The research was conducted in MIN 2 Kulon Progo. The research instruments used were mathematics learning outcomes tests on addition and subtraction of fractions at the end of each cycle, observation sheets, and field notes. The research data were analyzed descriptively to obtain the mean or average and the percentage of completeness of student learning outcomes. While qualitative analysis was used to describe the results of the observations and field notes. The results showed an increase in the percentage of completeness of learning outcomes in each cycle. In the pre-cycle, the percentage of completeness of student learning outcomes was 20%, in cycle I it was 73%, and in cycle II it was 97%, so there was an increase in the percentage of completeness of learning outcomes by 23% from cycle I to cycle II.